Study of Predictive factors of public health based on job satisfaction in employees of Rasht city Health Service Centers - Farideh Kamali Dehkordi; Shahrokh Maghsoudi; Abdolhossein Emami Sigaroudi; Ehsan Kazemnejad Leili (Guilan University of Medical Sciences, 2015)
Abstract چمقدمه : نحوه ارتباط والدین با فرزندان با سبک فرزندپروری آنان ارتباط دارد.سبکهای فرزندپروری نقش مهمی در شکل گیری شخصیت بهنجار و نابهنجار در کودکان داشته و در صورت بکار گیری سبکهای ناکارآمد در تربیت کودکان می تواند منجر به پیامدهای منفی متعددی از جمله مشکلات رفتاری در آنان گردد.Introduction: Manpower providing health and treatment care has a crucial contribution to public health, therefore maintaining and improving the quality of health care providers is required for quality of providing service. An aspect that has impact on their health is occupation and job satisfaction. Objective: Present study is designed to examine predictive factors of public health based on job satisfaction of health service centers' employees. Methods: This study is a cross sectional descriptive-analytic study conducted in 2012. In this study, census method was used for sampling. 252 personnel of health centers participated in this study and data collection tool included three questionnaires of Job Description Index (JDI), General Health Questionnaire (GHQ) and demographic characteristic questionnaire which were used after establishment of its validity and reliability. Data was analyzed using descriptive and analytical tests (Mann Whitney- Kruskal Wallis. Rیافته ها: نتایج نشان داد که سبک فرزندپروری مقتدرانه هم با نمره کل مشکلات رفتاری درونی سازی (003/RResults: Findings showed that only 47.6% of staff had good general health. About 63.16% of employees were satisfied most level of satisfaction was in colleague domain (76.83%) and least level of satisfaction was in salary domain (41.5%). Results indicated that from domain studied, only related and predicted areas of public health were colleague domain (p<0.049) and work environment condition (p<0.043) therefore the chance of general health increased by increasing level of satisfaction with colleague and work condition. Among the demographic characteristics, education (p<0.043) and management position (p<0.035) were identified as predictors of public health. Conclusion: In attention to obtained results, it can be said that the relationship between work and health is mutual and for improving the two concepts, planning and appropriate interventions are needed. And this intervention can lead to increased job satisfaction and staff physical and mental health.